Karakteristik Individu, Pola Komunikasi, dan Efektivitas Kinerja Kelompok Ternak Ngudirejeki - Farina Ekarini; Amiruddin Saleh; Muladno Muladno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Animal husbandry is a form of business activity to create prosperity. In practice, each breeder has its own way of building a vision that is sharing knowledge with others. A communication pattern is considered to be a very important part of knowing how the knowledge transfer process can proceed properly. Therefore, the study aims to analyze the characteristics of breeder group members, patterns of communication between livestock group members, and the effectiveness of livestock group performance. The research method was carried out in a quantitative survey through a questionnaire and data collection by interview techniques. The results obtained are: 1) a general description of the characteristics of members of the Ngudirejeki livestock group dominated by middle-aged men with the last education of high school graduates and have low experience of raising livestock and moderate livestock ownership (4–7 cattle); 2) more often apply interpersonal communication patterns; and 3) have a high level of effectiveness in performance with a group alert status of 93.3%. Keywords: animal herds, communication patterns, performance effectiveness